Quasi Ballistic Electron Reflection in Low-dimensional Semiconductor for Terahertz Signal Generation - Badrul, Iman Abidin (2019)
Graphene is in the forefront of low dimensional materials due to its high electron mobility in comparison to bulk materials because it has a Dirac cone band structure. Single layer silicon, silicine also has a similar Dirac cone structure as graphene. Manipulation of these materials gather a lot of interest from researchers. To investigate the electron transport properties in a monolayer freestanding graphene and silicene, an Analytical Band Monte Carlo (AMC) model has been developed. The energy band structure utilised in this model focused on the linear band dispersion close to the Dirac point. The AMC model is validated via comparison to the Full Band Monte Carlo (FMC) results such as electron mobility and drift velocity. In comparison to the FMC method, the AMC model requires significantly less computational time. The effects of carrier concentration in monolayer graphene and silicene were investigated in this study. It is found that a higher carrier concentration will degrade the steady-state drift velocity. Additionally, the carrier concentration has a noticeable effect on the electron mobility and mean free path. Higher carrier concentrations result in lower electron mobility and longermean free path. This is attributed to the collective effects of degeneracy and the dependency of the scattering rate and electrons energies. The electron mobility and mean free path for silicene are far inferior to graphene due to the higher phonon scattering rate. Particularly, graphene has negligible low optical and acoustic out-of-plane (ZA and ZO) scattering compared to silicene. The AMC model was further extended to explore the possibility of THz signal generation by using Quasi-Ballistic Electron Reflection (QBER). As a proof-of-concept, a numerical model was developed to study the electron oscillation in graphene or silicene confined between two energy barrier of infinite height. Due to the high electron mobility and long mean free path, QBER device based on graphene is able to produce radiation with peak frequency up to 1.6 THz and the frequency of the radiation can be varied by controlling the device length. On the other hand, the simulation results show that silicene is not a promising material in producing THz signal using the QBER concept due to short mean free path and high phonon scattering rate which lead to rapid loss of electron energy during the transport.